Evaluation of cross‐linked gelatin as a bulking agent for the management of urinary sphincter mechanism incompetence in female dogs. (20th July 2020) - Chen, Hilla; Shipov, Anna; Segev, Gilad
Abstract: Background: Bulking agent implantation is a minimally invasive intervention for the management of urethral sphincter mechanism incompetence (USMI). Hypothesis/Objectives: To evaluate the efficacy and safety of the novel bulking agent VetFoam for the management of urinary incontinence in female dogs diagnosed with USMI. Animals: Fifteen client‐owned female dogs. Methods: Prospective study. Female dogs diagnosed with USMI, refractory, or unamenable to medical treatment were included. VetFoam was injected under endoscopic guidance into the urethral submucosa. Continence score was evaluated before and after the procedure and monthly thereafter. Results: Twenty‐two injection procedures were performed in 15 dogs (5 dogs underwent >1 procedure). Median age of all dogs at the time of the procedure was 111 months (range, 18‐180). Median continence score significantly increased after, compared with before bulking agent injection (1.5; range, 1.0‐3.5 versus 4.0; range, 1.5‐5 respectively; P < .001; effect size, 2.6). Continence was achieved in 13/15 (87%) dogs after the first procedure and in 7/7 (100%) repeated procedures. Overall, 20/22 (91%) procedures resulted in high (≥4) continence scores at time of first follow‐up. Mean duration of continence was 11.1 months (SD, 10.7) after the first injection. One dog (7%) developed self‐limiting stranguria, pollakiuria, and tenesmus while no other apparent adverse effects were recognized in the other dogs. Conclusions and Clinical Importance: VetFoam is an apparently safe, effective novel bulking agent, which can be used as an alternative for the management of USMI.